Slovenski podjetniški observatorij 2004. Del 1 - Rebernik, Miroslav; Močnik, Dijana; Rus, Matej; Dajčman, Silvo (2004)
Slovenian Entrepreneurship Observatory 2004. Part 1. This Observatory provides an overview and analysis of the current situation in small and medium-sized enterprises (SMEs) in 2003. In monograph, we first analysed all Slovenian enterprises in 2003 and then we compared the situation in Slovenian entrepreneurship with European. Within Slovenian Entrepreneurship Observatory, enterprises are studied in a way in which all enterprises are taken into consideration: companies as well as sole proprietors; namely micro enterprises without employees, micro enterprises with 1 to 9 employees, small enterprises with 10 to 49 employees, medium sized enterprises with 50 to 249 employees and large enterprises with 250 and more employees. In Slovenia in 2003, 93,233 enterprises was active − employed more than 556,000 people. On average, most enterprises operated in distributive trades (motor trades, wholesale trade and retail trade) (24%). Beside the number of companies and their size also the number of employees was analysed, value added, labor costs and also some indicators of Slovenian economy compared to Europe was provided.
Keywords: demografija MSP; • mala in srednje velika podjetja; primerjalna analiza; dodana vrednost; stroški dela; SME Demography; Small and Medium-sized Enterprises; Comparative Analysis; Value added; Labor costs